Evaluation of rapid cell division in non‐uniform cell cycles. (15th July 2015) - Lee, Juyun; Jeon, Wonju; Chang, Man; Han, Myung‐Soo
<x xml:space="preserve">Abstract</x> To better understand the mechanisms of development of harmful algal blooms (HABs), accurate estimates of species‐specific in situ growth rates are needed. HABs are caused by rapid cell division by the causative microorganisms. To accurately estimate the in situ growth rates of harmful algae having non‐uniform and/or irregular cell cycles, we modified a standard equation based on the cell cycle, and calculated the in situ growth rate to describe the process of bloom development in nature. Sampling of a developing bloom of Heterosigma akashiwo in Pohang Bay, Korea, was conducted every 3 h from 15:00 on August 2 to 07:00 on August 4, 2006. The amount of H. akashiwo DNA was measured using flow cytometry following tyramide signal amplification‐fluorescence insitu hybridization. On August 2, the percentage of G1 phase cells decreased from 15:00 to 19:00 then increased until 22:00; it then decreased until 07:00 on August 3, followed by an increase to 10:00. This indicates the ability of the cells in nature to undergo more than one round of division per day. During the following night two rounds of division did not occur. The in situ growth rates estimated using the modified equation ranged from 0.31 to 0.53 d−1. We conclude that the use of this equation enables more accurate estimates of bloom formation by rapidly dividing cells.